2023
DOI: 10.1038/s41430-023-01303-w
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum albumin concentrations over 7 days in medical inpatients with and without nutritional support. A secondary post-hoc analysis of a randomized clinical trial

Abstract: Background Serum albumin concentrations are frequently used to monitor nutritional therapy in the hospital setting but supporting studies are largely lacking. Within this secondary analysis of a randomized nutritional trial (EFFORT), we assessed whether nutritional support affects short-term changes in serum albumin concentrations and whether an increase in albumin concentration has prognostic implications regarding clinical outcome and response to treatment. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Whilst current evidence does not support the use of IV albumin treatment, an important modifiable target to increase albumin levels is nutritional intervention. Randomised control trials investigating nutritional intervention remain limited in patients with AIS [25,26], potentially driven by a lack of consensus on the benefits and optimal use of nutritional support in medical patients with acute and severe illness [27,28]. A small randomised controlled trial (RCT) recently showed improved albumin levels in patients with HF who received oral branched-chain amino acids (BCAAs) granules added to standard therapy for 28 days until discharge compared to nine controls [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst current evidence does not support the use of IV albumin treatment, an important modifiable target to increase albumin levels is nutritional intervention. Randomised control trials investigating nutritional intervention remain limited in patients with AIS [25,26], potentially driven by a lack of consensus on the benefits and optimal use of nutritional support in medical patients with acute and severe illness [27,28]. A small randomised controlled trial (RCT) recently showed improved albumin levels in patients with HF who received oral branched-chain amino acids (BCAAs) granules added to standard therapy for 28 days until discharge compared to nine controls [29].…”
Section: Discussionmentioning
confidence: 99%
“…A RCT in 2020 demonstrates no rise in albumin after supplementation with whey protein in patients who have suffered a stroke [26]. A secondary post hoc analysis of the EFFORT RCT, concluded that in the short-term, a rise in serum albumin levels occurred regardless of nutritional support [27]. Further studies suggest that albumin levels may not depend on nutritional support or albumin treatment but rather the resolution of disease and inflammation [28].…”
Section: Discussionmentioning
confidence: 99%
“…O mesmo efeito não foi verificado em relação à albumina provavelmente porque a intervenção durou 10 dias, e a meia-vida da albumina é de 19 dias. Esse resultado é compatível com outros, que indicam que intervenções nutricionais não aumentam as concentrações de albumina em curto prazo, (BOESIGER et al, 2023) porém são suficientes para aumentar os valores de pré-albumina (DI RENZO et al, 2019).…”
Section: Discussionunclassified
“…Inflammation caused by primary diseases and surgical injury can affect the effectiveness of nutritional support, and changes in traditional nutritional indicators are not sensitive or comprehensive enough to reflect short-term improvements in nutritional status. Albumin, one of the traditional indicators, is considered an inflammation marker rather than a nutritional marker 32 , 33 . In recent years, several high-quality studies have defined the primary endpoint for determining the effectiveness of nutritional intervention as whether it can improve perioperative outcomes, mainly mortality in non-surgical patients and the incidence of postoperative infection complications in surgical patients 7 , 34 .…”
Section: Discussionmentioning
confidence: 99%